Articulando saberes no ensino de ciências usando o tema quelônios em escolas ribeirinhas no município de Parintins - Am - Fonseca, Ana Paula Melo (2019)
This study deals with questions related to popular and scholastic knowledge coming from riverside schools, bringing the articulation of these knowledge to the teaching of sciences. Therefore, the objective of this research is to understand how the flow of information in the school occurs, and the connection of popular and scholarly knowledge, using the theme of the Amazonian chelonians in riverside schools of Parintins-AM. The methodology of the study is molded qualitative research with a phenomenological approach. Research techniques were used: participant observation, oral and written oral interview, pre and post-test questionnaires, as well as drawing activities with children's reports about drawings. For the analysis of the data was used content analysis, where it was established categories of analysis for the construction of indicators of knowledge in riverside context. We point out that the knowledge derived from the daily life of children is elements that facilitate teaching and learning in the classroom. The shared knowledge originates new discoveries and questions giving the opportunity for the student to build their knowledge. The articulation of knowledge is carried out with the community and parents of the students in a participative way, with greater visibility during the execution of the project of preservation of chelonians in the communities